Effect Of The Application Of Different Cooking Periods On The Physicochemical Properties And Microbial Safety Of Hot Pepper Sauce - Nartey, Ebenezer Narteh; Tei-Mensah, Emmanuel; Adusei, Stephen; Asante, Doreen; Abaati, Charity (IPTEK The Journal for Technology and Science, 2025)
Hot pepper sauce is a frequently used product in most Ghanaian homes, schools, and restaurants, which occasionally serves as condiments. The cooking period during the production process of hot pepper sauce results in physicochemical changes, which affect the quality and safety of the sauce. The study seeks to determine the effect of the application of different cooking times on the physicochemical properties and microbial safety of hot pepper sauce. The cooking periods were 10 minutes, 20 minutes, 30 minutes, and 1 hour for samples A, B, C, and D. Standard physicochemical and microbiological techniques were employed in the various analysis. Sample D (1 hour cooked) recorded the least moisture and ash content, insoluble acid ash, and a statistically significant acid value (P<0.5) to the other samples (A, B, and C). The total viable count assay indicated anaerobic microorganisms in all the samples assessed, with sample D exhibiting very few microbial populations compared to the others. Staphylococcus species were detected in samples A and B only but undetected in samples C and D. Also, total coliform and Clostridium perfringens were unobserved in any of the samples. Generally, sample D had the best overall acceptability rate, with sample A having the least. This study, therefore, supports the patronization of the hour-cooked hot pepper sauce (sample D) with greater quality, longer shelf-life, and safety.